ILLUSTRATION OF EDUCATIONAL CONCEPTS FOR CHILDREN IN LEARNING PROBLEMS - Mufidul Abror; An'im Fattach (Sean Institute, 2023)
Education is a human right, therefore education must be enjoyed by all Indonesian citizens. Children with learning problems also have the same rights in obtaining proper education. Children with learning problems include children with special needs, this means that the form of educational services provided is also special. The education system for children with special needs is currently more embodied in the form of special education arrangements. However, there is a tendency for the education system to lead to a very flexible mainstreaming concept. In line with this concept, a model of extraordinary education services emerged called the inclusion model , which emphasizes full integration, eliminating the label of children (normal or not normal) with the principle of education for all .